Effects of intermittent polyelectrolyte addition on water quality in direct filtration - (:unkn) unknown (IWA PUBLISHING, 2011)
The effects of intermittent polyelectrolyte addition on the quality of effluent water and on the development of filter headloss were studied. Anionic and cationic polyelectrolytes were applied to two similarly constructed pilot sand filters. The surface water used in the study was obtained from Omerli, which is one of the main drinking water reservoirs of Istanbul. Six sets of experiments were carried out. The objective of the experiments in the first three sets was to determine the type and dose of suitable polyelectrolyte. The polyelectrolytes were then added intermittently and continuously in the last three sets. Intermittent addition of polyelectrolyte produced better effluent quality and reduced the polyelectrolyte consumption by half with much less headloss. Ives' Filterability Index, which incorporates the important filtration design parameters such as effluent quality, the headloss and the velocity of filtration into a dimensionless number, was used for the comparison of the experimental results.
Keywords: direct filtration; filter headloss; intermittent polyelectrolyte addition; particle count; polyelectrolyte; turbidity; PERFORMANCE